2020
DOI: 10.1177/1090198120914250
|View full text |Cite
|
Sign up to set email alerts
|

School Climate as a Universal Intervention to Prevent Substance Use Initiation in Early Adolescence: A Longitudinal Study

Abstract: Initiation of substance use often starts during adolescence, with tobacco and alcohol use frequently preceding the use of marijuana and other illicit drugs. Studies suggest that a positive school climate may prevent substance use while promoting healthy student behaviors. The purpose of this study was to determine the longitudinal associations between school climate and substance use initiation in a group of middle school students. Parallel latent growth curve modeling was used to examine changes among study v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…Elkins et al found that schools that frequently set and enforced rules regarding drug use tended to have lower rates of non-prescription steroid use [ 1 ]. Daily et al found that schools that had a positive climate prevented substance-use initiation [ 35 ]. Because steroid use in adolescents tends to be a part of a cluster of risk taking and substance use behaviors, interventions targeting the school level may be an effective and efficient strategy to lower initiation of steroid abuse among high school students.…”
Section: Discussionmentioning
confidence: 99%
“…Elkins et al found that schools that frequently set and enforced rules regarding drug use tended to have lower rates of non-prescription steroid use [ 1 ]. Daily et al found that schools that had a positive climate prevented substance-use initiation [ 35 ]. Because steroid use in adolescents tends to be a part of a cluster of risk taking and substance use behaviors, interventions targeting the school level may be an effective and efficient strategy to lower initiation of steroid abuse among high school students.…”
Section: Discussionmentioning
confidence: 99%
“…A positive school climate is a very important trait in the promotion of academic success, favoring not only academic achievement [ 12 , 13 , 14 , 15 ], but also prosocial behavior [ 16 , 17 ], the development of self-identity and self-esteem [ 18 ], delayed drug use [ 19 ], a reduced probability of assaults [ 20 ], and the prevention of behavioral problems [ 21 ]; it is also related to tolerance towards ethnic diversity [ 22 , 23 ]. In contrast, a negative school climate is associated with truancy [ 24 ], bullying [ 25 , 26 ], and school violence [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in schools with deteriorated relationships, various problems can arise both at the student level, through bullying [ 33 ], school violence [ 27 ], and substance use [ 19 ], as well as at the teacher level, through the victimization [ 34 ] and bullying of teachers [ 35 ]. When teacher–student social relationships are positive, they can significantly reduce the impact of the victimization produced by bullying among students [ 36 ] and promote socio-emotional development [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a number of longitudinal studies have assessed student-and school-level changes in SC over time (e.g., Camacho et al, 2018;Coelho et al, 2020;Daily et al, 2020;Luengo Kanacri et al, 2017;Wang & Dishion, 2012). A key assumption of these longitudinal studies is measurement invariance of scale scores across waves of data collection.…”
mentioning
confidence: 99%